Differential and Integral Operators on Appell’s Matrix Functions - Batahan, R. S. (Author) Metwally, M. S. (مجلة الأندلس للعلوم الاجتماعية والتطبيقية, 2023)
Differential and Integral Operators on Appell’s Matrix Functions